Maintenance of Voluntary Self-regulation Learned through Real-Time fMRI Neurofeedback - Robineau, Fabien; Meskaldji, Djalel E.; Koush, Yury; Rieger, Sebastian W.; Mermoud, Christophe; Morgenthaler, Stephan; Van De Ville, Dimitri; Vuilleumier, Patrik; Scharnowski, Frank (Frontiers in Human Neuroscience, 2017)
Neurofeedback based on real-time functional magnetic resonance imaging (fMRI) is an emerging technique that allows for learning voluntary control over brain activity. Such brain training has been shown to cause specific behavioral or cognitive enhancements, and even therapeutic effects in neurological and psychiatric patient populations. However, for clinical applications it is important to know if learned self-regulation can be maintained over longer periods of time and whether it transfers to situations without neurofeedback. Here, we present preliminary results from 5 healthy participants who successfully learned to control their visual cortex activity and who we re-scanned 6 and 14 months after the initial neurofeedback training to perform learned self-regulation. We found that participants achieved levels of self-regulation that were similar to those achieved at the end of the successful initial training, and this without further neurofeedback information. Our results demonstrate that learned self-regulation can be maintained over longer periods of time and causes lasting transfer effects. They thus support the notion that neurofeedback is a promising therapeutic approach whose effects can last far beyond the actual training period.